2022
DOI: 10.21733/ibad.961403
|View full text |Cite
|
Sign up to set email alerts
|

Uzaktan Eğitim İngilizce Dersi Kelime Öğretiminde Web 2.0 Araçları Kullanımının Öğrenci Başarısına ve Tutuma Etkisi

Abstract: 1-Araştırmacıların katkı oranı eşittir. 2-Makalenin yazarları arasında çıkar çatışması bulunmamaktadır. 3-Araştırma Düzce Üniversitesi Bilimsel Araştırma ve Yayın Etik Kurulu Komisyonu tarafından çalışmanın amacı, yöntemi, veri kaynakları ve veri toplama araçları açısından değerlendirilmiş olup, Komisyonun 30.03.2021 tarih ve 06 nolu toplantısında alınan 2021/84 nolu kararıyla etik açıdan uygun olduğuna karar verilmiştir. 4-Bu makalede araştırma ve yayın etiğine uyulmuştur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…When the achievement test results of the experimental and control groups after the application were compared, it was determined that there was a significant difference between the achievement scores of the experimental group students in which Web 2.0 applications were used in chemistry course teaching. Similarly, many studies have shown that Web 2.0 applications have a significant impact on students' academic achievement (Akkaya, 2019;Almalı, 2020;Can, 2021;Demirel & Aslan, 2014;Köse et al 2021;Türegün et al, 2022). For example, in Köse et al (2021) study investigating the effect of Web 2.0 applications -supported argumentation on the academic achievement of secondary school students on the subject of force and energy, they determined that the experimental group students were more successful than the control group students.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When the achievement test results of the experimental and control groups after the application were compared, it was determined that there was a significant difference between the achievement scores of the experimental group students in which Web 2.0 applications were used in chemistry course teaching. Similarly, many studies have shown that Web 2.0 applications have a significant impact on students' academic achievement (Akkaya, 2019;Almalı, 2020;Can, 2021;Demirel & Aslan, 2014;Köse et al 2021;Türegün et al, 2022). For example, in Köse et al (2021) study investigating the effect of Web 2.0 applications -supported argumentation on the academic achievement of secondary school students on the subject of force and energy, they determined that the experimental group students were more successful than the control group students.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…For example, in Köse et al (2021) study investigating the effect of Web 2.0 applications -supported argumentation on the academic achievement of secondary school students on the subject of force and energy, they determined that the experimental group students were more successful than the control group students. Türegün et al (2022) found that the use of Web 2.0 tools in the distance education process increased vocabulary learning achievement in English lessons.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Web 2.0 technology tools take students away from traditional classroom environments and enable them to be active, and to share, and develop their highlevel thinking skills. Through these technologies, students also provide feedback, corrections, and opportunities for self-evaluation in online environments (Türegün Çoban & Adıgüzel, 2021;Kayaduman & Delialioğlu, 2021;Gündüzalp, 2021;Karakuş & Er, 2021;Gündüzalp, 2021b;Altunışık & Aktürk, 2021;Timur, Yılmaz & Küçük, 2021;Ledger & Fischetti, 2020). Such technologies were investigated by Can (2021) who examined the use of Edmodo-supported conceptual cartoons, one of the web 2.0 tools, in a 5th-grade science lesson, and as a result of the research, he determined that the application in question contributed to the effective, permanent, and rapid learning of the students.…”
mentioning
confidence: 99%